2010
DOI: 10.1002/arch.20395
|View full text |Cite
|
Sign up to set email alerts
|

JH biosynthesis by reproductive tissues and corpora allata in adult longhorned beetles, Apriona germari

Abstract: We report on juvenile hormone (JH) biosynthesis from long-chain intermediates by specific reproductive tissues and the corpora allata (CA) prepared from adult longhorned beetles, Apriona germari. The testes, male accessory glands (MAGs), ovaries, and CA contained the long-chain intermediates in the JH biosynthetic pathway, farnesoic acid (FA), methyl farnesoate (MF), and JH III. The testes and ovaries, but not CA, produced radioactive JH III after the addition of (3)H-methionine and, separately, unlabeled meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…This result suggests that mfe expression in other tissues reduces the difference in overall body expression. Consistent with this possibility, mfe expression has been detected in the ovaries of nurses honey bee ( Niu et al, 2014 ), and JH synthesis has been reported in the ovaries of beetles ( Tian et al, 2010 ) and mosquitoes ( Borovsky et al, 1994 ).…”
Section: Discussionsupporting
confidence: 57%
“…This result suggests that mfe expression in other tissues reduces the difference in overall body expression. Consistent with this possibility, mfe expression has been detected in the ovaries of nurses honey bee ( Niu et al, 2014 ), and JH synthesis has been reported in the ovaries of beetles ( Tian et al, 2010 ) and mosquitoes ( Borovsky et al, 1994 ).…”
Section: Discussionsupporting
confidence: 57%
“…In the mosquito A. aegypti, JH was shown to be synthesized de novo in the male accessory gland (Borovsky et al, 1994). In the longhorned beetle Apriona germari, JH was reported to be synthesized in the adult testes, male accessory glands, and ovaries (Tian et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The CA has been considered the only source of JH in insects, including honey bees (Sullivan et al ., ). Although JH biosynthesis has also been shown in ovaries of beetles (Tian et al ., ) and mosquitoes (Borovsky et al ., ), Bomtorin et al . () recently showed that expression of mfe in worker bee ovaries is much lower compared with in the CA, suggesting that the ovarian contribution to overall circulating JH titres is insignificant.…”
Section: Discussionmentioning
confidence: 99%